"A Healthy Nationalism": The Inclusion of Indigenous Australians in the Federal Cultural Policymaking of the 1960s and 1970s. Issue 3 (3rd July 2021) - Foster, Eleanor
ABSTRACT: This article argues that the inclusion of Indigenous Australian arts within federal cultural policymaking transitioned during the 1960s and 1970s from a salvage paradigm of value towards policies articulating self-determined Indigenous representation and the potential for a "healthy nationalism". The Australian Institute of Aboriginal Studies (1964), the Aboriginal Arts Board (1973) and their joint proposal for a Gallery of Aboriginal Australia (1975) form the basis of this discussion and are representative of federal initiatives to "salvage", collect and promote Indigenous Australian culture within the national image. Despite commitments to controlling Indigenous representations as a "tribal" phenomenon, the late 1960s saw cultural nationalism flourish and Indigenous Australians achieve symbolic recognition in the 1967 Referendum. By the 1970s, shifting scholarly paradigms transformed artistic patronage towards a policy of self-determination for the arts as Indigenous activism succeeded in forcing change within cultural institutions. Proposals for a Gallery of Aboriginal Australia typified the aspirations of policymakers who sought a greater Indigenous emphasis in Australia's cultural identity and, for Indigenous people, promised to reform colonial representations. The gallery's delayed emergence revealed the declining cultural vision of previous decades as Indigenous Australians continued to push the structures of governance to value their cultural knowledge.